2008
DOI: 10.1186/1471-2407-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Endocan tumorigenic properties after alternative splicing of exon 2

Abstract: Background: Endocan was originally described as a dermatan sulfate proteoglycan found freely circulating in the blood. Endocan expression confers tumorigenic properties to epithelial cell lines or accelerate the growth of already tumorigenic cells. This molecule is the product of a single gene composed of 3 exons. Previous data showed that endocan mRNA is subject to alternative splicing with possible generation of two protein products. In the present study we identified, and functionally characterized, the alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…High levels have also been detected in patients with cancer (Aitkenhead et al 2002;Depontieu et al 2008;Grigoriu et al 2006;Huang et al 2009;Scherpereel et al 2003;Zuo et al 2008). Nonetheless, high levels may be of relevance for the promotion of systemic inflammation, as endocan mediates the recruitment of circulating lymphocytes to inflammatory sites as well as leukocyte adhesion and activation (Bechard et al 2001b).…”
Section: Endocanmentioning
confidence: 99%
“…High levels have also been detected in patients with cancer (Aitkenhead et al 2002;Depontieu et al 2008;Grigoriu et al 2006;Huang et al 2009;Scherpereel et al 2003;Zuo et al 2008). Nonetheless, high levels may be of relevance for the promotion of systemic inflammation, as endocan mediates the recruitment of circulating lymphocytes to inflammatory sites as well as leukocyte adhesion and activation (Bechard et al 2001b).…”
Section: Endocanmentioning
confidence: 99%
“…The recent identification of endocan’s expression and active secretion by tumor cells, which tend to express endothelial cell-associated genes, also suggests its possible pro-tumorigenic role, with higher degrees of expression being associated with increased tumor invasiveness 22,38. Not surprisingly, given the biological significance of the molecule’s DS, only fully glycanated endocan promotes tumorigenesis, although not without the contribution of its polypeptide 38,39…”
Section: Endocan: General Knowledgementioning
confidence: 99%
“…The gene can be cut to encode two endocan products with distinct expression: One is a mature endocan molecule, including a complete core protein with a F113 and F116 phenylalanine-rich region and a DSPG single-strand (proteoglycan-rich, single-stranded and phenylalanine pool are associated with endocan tumor promotion); the second product is an endocan molecule lacking the exon 2 promoter region, known as endocanΔ2. Depontieu et al (7) showed that endocanΔ2 does not promote tumor growth. EndocanΔ2 has the same endocan N-and C-terminus, but lacks the exon 2 encoding 50 amino acids.…”
Section: Introductionmentioning
confidence: 99%